System architecture for applying Malik Bennabi’s ruler on intellectual property of Islamic finance and banking - Othman, Roslina; Noordin, Mohamad Fauzan; Gusmita, Ria Hari; Zulkifli, Zahidah; Tengku Sembok, Tengku Mohd (IEEE, 2016)
This paper presents our work in designing a system architecture for applying Malik Bennabi’s ruler on Intellectual Property (IP) of Islamic Finance and Banking. We choose journal article as IP for Islamic Finance and Banking. There are several components in the architecture starting from IP retrieval, structure extraction, structure classification, structure summarization, and Knowledge-based similarity measuring. The architecture will be implemented in order to measure all journal article’s content and group them into two categories namely Useful and Harmful.